Encountering the State: Women and divorce in Riyadh, Saudi Arabia - Zina Sawaf (Arabian Humanities)
In the post-September 11 era, the state in Saudi Arabia is said to be feminizing itself by promoting inclusive reform vis-à-vis women. Since King ʿAbdallah’s reign, and through Prince Muḥammad bin Salmān’s recent and ambitious roadmap of socio-economic reforms, the monarchy has been championing women’s causes. This article seeks to move beyond a state-centric approach that focuses on the role of the Saudi state, actors and institutions. Rather, it takes an ethnographic view point to explore how the state’s feminization of itself unfolds in the everyday encounters and interactions between women divorcées and the processes, offices and officials of the state in Riyadh, Saudi Arabia. Simply by engaging the state and continually re-interpreting what it might offer them in terms of rights and resources, divorcées are able to draw new boundaries around their private lives. Consequently, it matters not so much that state actors and institutions espouse women’s positions in various realms, but rather that this so-called feminization enables women to act upon, interpret and imagine differently family and sexual life, and crucially, ways of being with and for others.